Reading Between the Lines - Sturma, Madeleine; Emmelhainz, Celia (Qualitative and Quantitative Methods in Libraries, 2020)
Academic libraries want to collect the materials most useful to researchers, yet how can libraries know how successful they are? While Berkeley’s George and Mary Foster Anthropology Library collects data on which books circulate, it is difficult to evaluate how materials are actually being used to further the discipline of anthropology. In this article, we examine sources cited by our a) faculty members, b) dissertation writers, and c) honors thesis students to better understand how anthropologists read when conducting research. This paper compares materials used across subfields and research levels to highlight patterns in citations within this discipline, leading to new insights that will improve collection development among anthropology librarians.